Языковые стереотипы в Аксиологическом лексиконе славян и их соседей (на материалах к описанию концепта СЕМЬЯ) - Fedorova, Liudmila (Wiener Slawistischer Almanach, 2023)
The article focuses on the Axiological Lexicon of Slavs and their Neighbors, a project of the Polish ethnolinguistic school. Taking this lexicon as an example, the present paper discusses the principles underlying the construction of a new type of dictionary, central to which are the value concepts in different linguistic cultures. The role of linguistic stereotypes in the construction of the cognitive definition of concepts is noted. The illustrative material presented in the article consists of fragments of the description of the concept FAMILY in Russian against the background of other languages.